Workplace Self-Care Networks in The Literature From 2019 To 2022 - GarcÃa Lirios, Cruz (Accounting Department,, 2022)
Purpose — The document explores the literature published from 2019 to 2022 regarding occupational self-care. It proposes that the risks and contagion, illness, and death reduced the accidents and illnesses in the local occupational field. Design/methodology/approach—A documentary, cross-sectional, exploratory, and correlational study was conducted using a sample of findings published in journals indexed to international repositories, considering the keywords